Resource utilization method of valuable metals in copper slag tailings

Through the technology of coupling inorganic acid leaching and ultrasonic action, combined with cyclic boiling water leaching, microwave heating and hydrofluoric acid pressurization dissolution method and high-frequency electromagnetic field-assisted magnetic separation, the low utilization efficiency of valuable metal resources in copper slag tailings is solved. The problem is that efficient and environmentally friendly resource recycling is achieved and valuable metal products with high purity are obtained.

CN119433220APending Publication Date: 2025-02-14KUNMING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411575082.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art has problems such as low efficiency, high cost, and environmental pollution in the resource utilization of valuable metals in copper slag tailings, making it difficult to achieve efficient and environmentally friendly resource recycling.

Method used

Using a new technology that couples inorganic acid leaching and ultrasonic action, copper slag tailings are treated through ultrasonic acid leaching, combined with circulating boiling water leaching, microwave heating and hydrofluoric acid pressurization dissolution method and high-frequency electromagnetic field-assisted magnetic separation to further purify and separate Valid metal.

Benefits of technology

It has achieved efficient leaching and separation of valuable metals in copper slag tailings, and obtained high-purity white carbon black, ferrous fine chemical products, ice-copper ore and zinc slag, which has significant environmental protection and economic value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433220A_ABST
    Figure CN119433220A_ABST
Patent Text Reader

Abstract

The invention discloses a resource utilization method of valuable metals in copper slag tailings, and relates to the technical field of metallurgy and tailing resource utilization, and the method comprises the following steps: (1) carrying out ultrasonic acid leaching treatment on the copper slag tailings to obtain a leaching solution and leaching residues; (2) the leaching residues are sequentially subjected to circulating violent boiling water leaching, microwave heating and hydrofluoric acid pressurized dissolution method purification and high-frequency electromagnetic field assisted magnetic separation, and then high-purity white carbon black is obtained; (3) carrying out reduction and complexing treatment on the leachate to obtain copper matte and filtrate; and (4) performing evaporative crystallization on the filtrate to obtain ferrite crystals and concentrated mother liquor, drying the ferrite crystals to obtain FeCl2, and adding a complexing agent into the concentrated mother liquor to obtain zinc slag. According to the method disclosed by the invention, the conventional burden of equipment investment and operation of enterprises is reduced, the process is clean and environment-friendly, secondary pollutants are not generated, complicated operations such as crushing, ball milling, large-amount alkalization, high pressure or oxidizing agents are not needed, high-grade and high-value realization of valuable components is realized, and 100% reduction of stacked tailings is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgy and tailings resource utilization, and in particular to a resource utilization method for valuable metals in copper slag tailings. Background Art

[0002] With the continuous improvement of the integrity of my country's copper industry chain and the completeness of copper product varieties, the output of refined copper will reach 12.99 million tons in 2023, of which about 90% of copper smelting enterprises adopt pyrometallurgical smelting, and on average, 2.2 tons of copper smelting slag tailings are produced for every ton of copper. At the same time, with the further popularization of copper matte slag flotation and copper extraction technology in recent years, the final industrial solid waste is copper slag tailings, and the total amount of slag is second only to iron tailings. Copper slag tailings are bulk solid wastes, with large quantities and wide areas, prominent environmental impacts, and broad prospects for utilization. They are the core areas of comprehensive resource utilization. However, at present, except for a small amount used in building materials, abrasives and cement additives, copper slag tailings are mainly stored, with a cumulative storage of more than 300 million tons. Under long-term wind, sun and rain, the toxic and harmful elements in the copper slag will seep into the land, causing great losses of valuable metal resources and environmental pollution.

[0003] Since the iron in the smelting slag is stored in the slag in the form of fayalite, the efficiency of magnetic separation after magnetization roasting to magnetic iron oxide is not high. The copper utilization rate in copper slag tailings is less than 12%, and the iron utilization rate is less than 1%. At present, the effective treatment methods for valuable metals in copper slag tailings are mainly pyrometallurgical depletion, mineral processing, wet leaching and combined smelting. Among them, the pyrometallurgical depletion process will produce a lot of flue gas pollution, and it is necessary to maintain high temperature for a long time, which consumes a lot of energy; the ore processing method has high requirements for the crystal growth and grinding fineness of copper slag, and cannot change the occurrence state of metals such as fayalite, making it difficult to enrich; the combined smelting method has a long process flow and low economic benefits. Obviously, these technologies have certain limitations; wet leaching is an important method for recovering valuable metals in copper slag. The valuable metal elements in the copper slag react with some added chemical leaching agents or biological solutions, and then separate the valuable metals from impurities through solid-liquid separation. It is an efficient and economical recovery method, which is mainly divided into oxygen pressure leaching, chlorination leaching, and direct acid / alkali leaching. Increasing the oxygen pressure in the oxygen pressure leaching method can increase the oxygen electrode potential and make the leaching reaction process more intense, but the high pressure needs to be in a closed environment, the investment is high, and the equipment requirements are high; the process of chlorination leaching of copper slag tailings is generally divided into two steps, the first is the generation of chlorine, and the chlorine reacts with the copper slag to selectively leach the valuable metals in the slag. The process has less corrosion to the equipment, but the chlorine produced will pollute the environment, which has great limitations; direct ammonia leaching uses ammonia-ammonium carbonate solution to leach copper and zinc. The copper recovery rate is high, but the volatilization loss is large, the selectivity is poor, and it is easy to cause pollution to the site.

[0004] In addition, ultrasonic strengthening, as one of the effective strengthening methods, shows good development and application prospects. Studies have shown that ultrasonic action can refine solid particles, and the turbulence generated by the collapse of ultrasonic microjets and cavitation bubbles affects the mineral structure, which can effectively destroy the structure of iron silicates and cause valuable metals to precipitate into the liquid phase. Valuable metals can then be extracted by extraction, ion exchange and other methods. This was once considered a more feasible technical route. However, under traditional conditions, the effect of ultrasonic combined with traditional acid leaching system to leach and recover valuable metals is not ideal. The gaps produced by ultrasonic destructive action are easily re-blocked by the colloidal substances generated by the reaction of organic acids or weak acids with silicates, and the dissolution effect of the leaching reaction channels produced by the gaps gradually fails, resulting in the fact that the effect of ultrasound in organic acid or weak acid systems is not obvious, and silicate has a greater impact on subsequent filtration and electrolytic deposition.

[0005] Obviously, the above-mentioned technologies all have certain limitations. Traditional copper matte slag is obtained by direct smelting. Now, after the slow cooling and flotation copper extraction process has been widely popularized, the copper residue can be reduced to 0.23-0.26%. The basic component ratio of copper slag tailings has changed greatly. For example, the Chinese invention with publication number CN101555551A proposes a method for comprehensive recovery of Fe, Cu and Si from copper smelting slag. Cu =0.35~4.6%, the solid-liquid ratio of copper slag to inorganic acid is 5:1~25:1 to prepare slurry, but a large amount of alkali must be added to the solution in the separation process after leaching until the pH = 6-9, the silicon dioxide recovery rate is 75%, the copper recovery rate is 76%, and the iron recovery rate is 85%. The obtained iron oxide phase and copper-containing phase have low grades, and the saturated calcium chloride contains more impurities such as arsenic and lead.

[0006] As can be seen from the above, the current leaching recovery process mainly for copper resources has gradually lost its practical effect and commercial value. Therefore, providing a stable and efficient resource utilization method for valuable metals in copper slag tailings is a technical problem that urgently needs to be solved in this field. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a method for resource utilization of valuable metals in copper slag tailings. The method of the present invention meets the conventional burden of enterprise equipment investment and operation, the process is clean and environmentally friendly, no secondary pollutants are generated, and no complex operations and high-cost conditions such as crushing and ball milling, large-scale alkalization, high pressure or oxidants are required. The valuable components are realized with high grade and high value and a 100% reduction in the accumulated tailings is achieved.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] A method for resource utilization of valuable metals in copper slag tailings comprises the following specific steps:

[0010] (1) treating the copper slag tailings by ultrasonic acid leaching to obtain a leaching solution and leaching residue;

[0011] (2) subjecting the leached residue of step (1) to sequential purification by cyclic boiling water leaching, microwave heating with hydrofluoric acid pressure dissolution method and high-frequency electromagnetic field assisted magnetic separation to obtain high-purity white carbon black;

[0012] (3) subjecting the leaching solution of step (1) to electron-rich material reduction and complexation treatment, and then obtaining matte and filtrate by oscillating flow reaction precipitation method;

[0013] (4) The filtrate in step (3) is subjected to evaporative crystallization to obtain ferrous salt crystals and a concentrated mother liquor, the ferrous salt crystals are dried by hot nitrogen circulation to obtain FeCl2, and a complexing agent is added to the concentrated mother liquor to obtain zinc slag.

[0014] In view of the deficiencies in the prior art, the present invention provides a process for complete reduction of copper slag tailings and comprehensive resource utilization of valuable metal elements. Through innovative reaction system design and reasonable resource recovery process flow, a new technology of coupling inorganic acid leaching and ultrasonic action is adopted. On the basis of synergistic efficiency enhancement, the technical barrier of incompatibility between ultrasonic method and silicic acid and orthosilicic acid products is effectively broken through. The response surface method is used to obtain effective operating parameters, and the leaching efficiency is effectively improved. When the reaction device is operated at full load, the purity of white carbon SiO2 is ≥95%, the purity of ferrous fine chemical products is ≥98%, the copper grade of matte is ≥61%, and the purity of zinc is ≥80%, all of which are high-grade and high-value products.

[0015] Preferably, in the ultrasonic acid leaching in step (1), the solid-liquid ratio is 1:2-20, the ultrasonic power is 300-800 W, the temperature is 55-105 ° C, the time is 2-5 h, and the stirring speed is 50-250 rpm;

[0016] The acid leaching uses hydrochloric acid, nitric acid, sulfuric acid or a mixture of two of them.

[0017] The invention has innovated a copper slag tailings resource recovery method that couples inorganic strong acid leaching with ultrasonic technology. It uses the synergistic effect of the strong acid system and ultrasonic means to effectively target the pain points of the existing copper slag tailings valuable metal resource recovery technology and achieve the three-in-one treatment of solid waste pollution. In the strong acid system, silica gel products that affect the gap reaction channels on the island crystal structure will not be generated. Therefore, to a certain extent, strong acid and ultrasonic auxiliary means have a synergistic effect.

[0018] The ultrasonic combined acid leaching of the present invention can achieve efficient leaching of valuable metals. Taking hydrochloric acid as an example, the reaction formula is as follows:

[0019] Fe2SiO4+4HCl=2FeCl2+2H2O+SiO2

[0020] Fe3O4+2HCl=FeCl2+H2O+Fe2O3

[0021] Fe2O3+6HCl=2FeCl3+3H2O

[0022] Preferably, the mass concentration of the strong acid is 20-100%;

[0023] The copper slag tailings also include pretreatments of screening and vacuum drying before ultrasonic acid leaching, which can improve subsequent processing efficiency and metal recovery rate.

[0024] Preferably, the temperature of the ultrasonic acid leaching is 75-115°C.

[0025] Preferably, the ultrasonic acid leaching in step (1) further comprises adding an oxidant, which can accelerate the mineral dissolution rate and shorten the time for the metal leaching of the contents to reach equilibrium, and the molar ratio of the oxidant to the measured iron element in the copper slag tailings is 1-3:1.

[0026] Preferably, the oxidant is at least one of H2O2, NaClO, NaClO2, ClO2, Cl2, and persulfate.

[0027] Preferably, the operation steps of the cyclic bumping water immersion in step (2) are: adding tap water to the leached residue at a solid-liquid ratio of 1:1-5, heating the tap water to boiling, and cooling it down with cold water to create bumping conditions, the bumping time is 1-3h, the rotor speed is 50-250rpm, so that the acid on the surface of the leached residue and the metal salt substances that have not been completely leached are fully dissolved, so that the purity of the silicon-containing substance in the leached residue is further improved;

[0028] Preferably, the microwave heating assisted hydrofluoric acid pressure dissolution method purification operation steps are: after the leached residue is prepared into a slurry at a solid mass fraction of 20-80%, a hydrofluoric acid solution is added, and the mixture is stirred for 1-2 hours under microwave-assisted heating conditions; then the microwave device is turned off, the mixed slurry is maintained at 55-85° C., and the mixture is continuously stirred for more than 30 minutes, and then a reducing agent is added for reduction under stirring and pressurizing conditions, and finally the mixture is washed with filtered water until the pH value of the washing liquid is close to neutral, so as to obtain relatively pure white carbon black (SiO2 content ≥ 90%);

[0029] The frequency range of the microwave is 1-50 GHz, the wavelength is 1 mm-1 m, the total amount of hydrofluoric acid added as solute is 1-10% of the mass of the slurry, the temperature of the microwave-assisted heating is 150-250° C., the stirring speed is 250-500 rpm, the pressurization condition is 0.1-0.5 MPa, and the reducing agent is sodium bisulfite, and the addition amount is 10-20 kg / t.

[0030] Preferably, the mixed slurry is heated in a water bath, an oil bath, an electric furnace, etc.

[0031] The magnetic field strength of the high-frequency electromagnetic field assisted magnetic separation is 480-1600 kA / m. The relatively pure white carbon black is first crushed, ground and screened before magnetic separation to control the particle size below 5 mm. After magnetic separation, high-purity white carbon black (SiO2 content ≥ 99%) is obtained. The high-frequency electromagnetic field adopts an optimized layout to improve the energy transfer efficiency, further separate the magnetic iron oxide from the leached slag, and improve the purity of the white carbon black.

[0032] Preferably, the amount of the electron-rich material added in step (3) and the Fe 3+ The molar amount in is equal; the time of addition is when the actual ferrous ion concentration is close to the saturated solubility during the cooling process, the reaction temperature is 30-50℃, and the time is 20min;

[0033] Preferably, the electron-rich material is at least one of hydroxylamine, metal organic framework materials (MOFs), quinone hydroquinone, organic acid and boron;

[0034] The molar ratio of the complexing agent to the zinc element measured in the leaching solution is 1-1.5:1;

[0035] The complexing agent is selected from methyl trioctyl ammonium chloride and / or oxalic acid.

[0036] The principle of the present invention is that Fe in the acid leaching solution 3+ The electron-rich material is fully reduced, and then a complexing agent is added to carry out a decontamination reaction. The heavy metal complex is filtered while hot, and after cooling, the precipitated copper ions are precipitated and then recycled as matte after an oscillating flow reaction, filtration, water washing, and drying. The remaining leachate after filtration can enter an evaporation crystallization process.

[0037] Preferably, the oscillating flow reaction precipitation method enhances radial mixing of materials in the reactor by applying periodic external oscillation to the copper ion-containing leachate, reduces axial back mixing of the fluid, and makes the residence time distribution close to that of plug flow under smaller net flow conditions, so that the precipitant material effectively reacts with the copper ions and is fully recovered.

[0038] Preferably, the conditions for evaporation and concentration are: evaporation at 70-85° C., concentration to 1 / 3-1 / 2 of the volume of the filtrate;

[0039] The crystallization adopts two crystallizations, dissolving the precipitated ferrous salt crystals and then performing a second crystallization, which can further improve the purity of the crystals;

[0040] The gas atmosphere of the hot nitrogen circulation drying is N2 protective atmosphere, and the conditions are: 50-200℃ circulation drying for more than 1h;

[0041] The concentrated mother liquor is diluted to Zn 2+ After the concentration reaches 1 g / L, the pH is adjusted to 2-5 and then the complexing agent is added;

[0042] The complexing agent is N263 and / or P2O4, and the final concentration is 0.6-1M.

[0043] Preferably, a buffer solution is added to the evaporation crystallization in step (4); an appropriate amount of the buffer solution protects the easily oxidizable divalent iron ion component, so that the crystallization step maintains a higher yield of ferrous chloride tetrahydrate.

[0044] The buffer solution is at least one of glycine, acetic acid, citric acid and EDTA.

[0045] Preferably, the measured Fe in the buffer solution and the filtrate is 3+ The molar ratio is 1-1.3:1.

[0046] Preferably, the concentration of the buffer solution is 0.5-2 mol / L.

[0047] Preferably, the copper slag tailings are tailings after pyrometallurgical copper smelting flotation, and its main chemical composition is Fe43-45%, Ca 0.6-2.8%, Zn 1.2-2.5%, Cu 0.27-3.1%, Al 1.8-2.3%, and Si 15-21%.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] The process of the present invention does not require fine grinding, has a small range of particle size requirements, and can completely leach valuable metals without the need for oxidants, closed pressurizing devices, magnetic separation and electrolytic deposition. The separation process does not require the addition of a large amount of alkali materials to neutralize concentrated acid, achieving 100% tailings reduction and simultaneously reducing operating costs and the risk of secondary pollution, and has significant environmental and economic value; the process flow is reasonably designed, easy to operate, low cost, simple equipment, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings in this description are only embodiments of the present invention.

[0051] Figure 1 The present invention is a process flow chart of a method for resource utilization of valuable metals in copper slag tailings. DETAILED DESCRIPTION

[0052] Embodiments of the present invention are described below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but are not to be construed as limiting the present invention.

[0053] Example 1

[0054] like Figure 1 The present invention provides a method for utilizing valuable metal resources in copper slag tailings, comprising the following specific steps:

[0055] (1) Pretreatment of copper slag tailings: 1 ton of copper slag tailings after pyrometallurgical copper flotation, with Fe43.3%, Si14.4%, Ca 2.3%, Zn 2.4%, Al 1.1%, Cu 0.24%, As 0.08% in the content, is simply screened to remove the agglomerated impurities with large particle size and adjust the particle size distribution, and then dried to reduce the humidity of the material and improve the subsequent acid leaching efficiency;

[0056] (2) adding the pretreated copper slag tailings into a 36% hydrochloric acid solution at a solid-liquid ratio of 1:5, and immersing them under ultrasonic stirring at a temperature of 85° C. for 3 h, with an ultrasonic power of 300 W and a stirring speed of 250 r / min, so that Fe3O4 in the iron-rich phase in the silicate gaps is effectively exposed and fully contacted with hydrochloric acid during the leaching process to fully dissolve the valuable metals in the leached slag, thereby obtaining a leachate and leached slag;

[0057] (3) The acid-leached residue was placed in a container with a certain pressure resistance, and tap water was added at a solid-liquid ratio of 1:2.5. The tap water was heated to boiling in the container, and the container wall was rinsed with cold water to quench it, thereby creating a boiling condition. The temperature was 60°C, the boiling time was 1h, and the rotor speed was 250rpm. The operating parameters of the microwave heating and hydrofluoric acid pressure dissolution method for purification were as follows: the microwave frequency range was 50GHz, the wavelength was 5mm, the leached residue was prepared into a slurry with a solid mass fraction of 20% and placed in a pressure vessel equipped with a mechanical stirrer, the speed was 300rpm, and the 40% hydrofluoric acid solution was 100k g, stirring the leached residue and the solution under microwave-assisted heating at 150°C for 1h, then turning off the microwave device, heating the leached residue and the solution in a water bath at 60°C and stirring continuously for more than 30min, then adding 15kg / t of reducing agent sodium bisulfite under the same stirring speed and 0.3MPa pressurization conditions, filtering and washing with water until the pH value of the washing liquid is close to neutral, and obtaining relatively pure white carbon black; the leached residue is crushed, ground and sieved, and the particle size is controlled to be less than 5mm, and then subjected to magnetic separation assisted by a high-frequency electromagnetic field with a magnetic field strength of 1000kA / m, and high-purity white carbon black is obtained after magnetic separation;

[0058] (4) Add the Fe 3+The hydroxylamine with the corresponding molar content is stirred at 60°C for 20 minutes for full reduction, and then 35 kg of oxalic acid is added for complex reaction. After full reaction for 10 minutes, heavy metal precipitates such as As and Pb are generated. The precipitated impurities are separated by hot filtration, and then the copper ions are precipitated by oscillating flow reaction. After filtration, washing and drying, matte is formed, and the filtrate is obtained at the same time;

[0059] (5) adding 20 L of 1 mol / L glycine solution to the filtrate, evaporating and concentrating at 80° C. to reduce the volume to 1 / 2 of the volume of the filtrate, recovering the HCl vapor and recycling it, and cooling the obtained concentrated solution for 20 min to precipitate high-purity ferrous chloride crystals, dissolving the precipitated ferrous chloride salt crystals and performing secondary crystallization to further improve the crystal purity; drying the purified ferrous chloride crystals in a gas atmosphere containing N2 at 80° C. for 1 h in a hot nitrogen cycle to obtain a ferrous chloride product;

[0060] The mother liquor after evaporation and concentration was added with 28kg N263 complexing agent, and after sufficient reaction, the zinc slag was obtained after filtration and drying;

[0061] After testing, the purity of SiO2 in white carbon black is 95.3%, and the silicon recovery rate is 98%; the purity of FeCl2 product is 98.2%, and the iron recovery rate is 91%; the copper grade of matte is 61.9%, and the copper recovery rate is 66%; the purity of zinc is 80.3%, and the zinc recovery rate is 81%.

[0062] Example 2

[0063] like Figure 1 The present invention provides a method for utilizing valuable metal resources in copper slag tailings, comprising the following specific steps:

[0064] (1) Pretreatment of copper slag tailings: 500 kg of copper slag tailings after pyrometallurgical copper flotation, containing 43.3% Fe, 12.3% Si, 1.9% Ca, 2.5% Zn, 1.8% Al, 0.30% Cu, and 0.02% As, were simply screened to remove agglomerated impurities with large particle sizes and adjust the particle size distribution, and then dried to reduce the moisture content of the material and improve the subsequent acid leaching efficiency;

[0065] (2) adding the pretreated copper slag tailings into a 70% sulfuric acid solution at a solid-liquid ratio of 1:5 and leaching at 85°C for 3 hours, with an ultrasonic power of 500 W and a stirring speed of 250 r / min, so that Fe3O4 in the iron-rich phase in the silicate gap is effectively exposed and fully contacted with sulfuric acid during the leaching process to dissolve the valuable metals in the leached slag to obtain a leachate and leached slag;

[0066] (3) The acid-leached filter residue is placed in a container with a certain pressure resistance, and tap water is added at a solid-liquid ratio of 1:2.5. The tap water is heated to boiling in the container, and the container wall is rinsed with cold water to quench it, thereby creating a boiling condition, the temperature is 60°C, the boiling time is 1h, and the rotor speed is 250rpm; the operating parameters of microwave heating and hydrofluoric acid pressure dissolution method purification are as follows: the microwave frequency range is 50GHz, the wavelength is 5mm, the leached residue is prepared into a slurry with a solid mass fraction of 20% and is placed in a pressure vessel equipped with a mechanical stirrer, 100kg of 40% hydrofluoric acid solution is added, and the mixture is stirred for 2 hours. The leached residue and the solution were stirred for 2 hours under microwave-assisted heating at 250°C, and then the microwave device was turned off, and the leached residue and the solution were heated to 60°C in an oil bath and stirred for more than 30 minutes, and then 15 kg / t of reducing agent sodium bisulfite was added under the same stirring speed and 0.3 MPa pressure conditions, and the solution was filtered and washed with water until the pH value of the washing solution was close to neutral, so as to obtain relatively pure white carbon black; the leached residue was crushed, ground and sieved, and the particle size was controlled to be less than 5 mm, and then magnetic separation was carried out under a high-frequency electromagnetic field with a magnetic field strength of 1000 kA / m to obtain high-purity white carbon black;

[0067] (4) Add the Fe 3+ Hydroxylamine with a corresponding molar content is stirred at 60°C for 20 minutes to be fully reduced, and then 60 kg of methyl trioctyl ammonium chloride is added to carry out a complex reaction. After fully reacting for 10 minutes, heavy metal precipitates such as As and Pb are generated. The precipitated impurities are separated by hot filtration, and then the copper ions are precipitated by an oscillating flow reaction. After filtering, washing and drying, matte is formed, and a filtrate is obtained at the same time;

[0068] (5) adding 20 L of 1 mol / L glycine solution to the filtrate, evaporating and concentrating at 80° C. to reduce the volume to 1 / 2 of the volume of the filtrate, recovering the HCl vapor and recycling it, and precipitating high-purity ferrous sulfate crystals from the obtained concentrated solution after cooling for 20 min, dissolving the precipitated ferrous sulfate crystals and performing secondary crystallization to further improve the purity of the crystals; drying the purified ferrous sulfate crystals in a gas atmosphere containing N2 at 80° C. for 1 h with hot nitrogen circulation to obtain ferrous sulfide;

[0069] The mother liquor after evaporation and concentration was added with 28kg N263 complexing agent, and after sufficient reaction, the zinc slag was obtained after filtration and drying;

[0070] After testing, the purity of SiO2 in white carbon black is 97.0%, and the silicon recovery rate is 98%; the purity of anhydrous ferrous sulfate is 98.4%, and the iron recovery rate is 93%; the copper grade of matte is 63%, and the copper recovery rate is 69%; the purity of zinc is 82.9%, and the zinc recovery rate is 85%.

[0071] Example 3

[0072] like Figure 1 The present invention provides a method for utilizing valuable metal resources in copper slag tailings, comprising the following specific steps:

[0073] (1) Pretreatment of copper slag tailings: 500 kg of copper slag tailings after pyrometallurgical copper flotation, containing 40.3% Fe, 10.9% Si, 2.1% Ca, 2.4% Zn, 1.1% Al, 0.27% Cu, and 0.04% As, were simply screened to remove agglomerated impurities with large particle sizes and adjust the particle size distribution, and then dried to reduce the moisture content of the material and improve the subsequent acid leaching efficiency;

[0074] (2) adding the pretreated copper slag tailings into a 38% hydrochloric acid solution at a solid-liquid ratio of 1:5, and immersing them for 3 hours under ultrasonic stirring at a temperature of 105°C to effectively expose Fe3O4 in the iron-rich phase in the silicate gaps and fully contact with hydrochloric acid during the leaching process. The ultrasonic power is 500W, the stirring speed is controlled at 250r / min, and 0.5M H2O2 is added to promote the oxidation process, fully dissolve the valuable metals in the leached slag, and obtain a leachate and leached slag;

[0075] (3) The acid-leached filter residue is placed in a container with a certain pressure resistance, and tap water is added at a solid-liquid ratio of 1:2.5. The tap water is heated to boiling in the container, and the container wall is rinsed with cold water to quench it, thereby creating a boiling condition, the temperature is 60°C, the boiling time is 1h, and the rotor speed is 250rpm; the operating parameters of microwave heating and hydrofluoric acid pressure dissolution method purification are as follows: the microwave frequency range is 50GHz, the wavelength is 5mm, the leached residue is prepared into a slurry with a solid mass fraction of 20% and is placed in a pressure vessel equipped with a mechanical stirrer, 100kg of 40% hydrofluoric acid solution is added, and the leached residue is slurried. The slag and solution are stirred for 2 hours under microwave-assisted heating conditions at a temperature of 200°C, and then the microwave device is turned off. The leached slag and solution are heated to 60°C in an electric furnace and stirred for more than 30 minutes. Then, under the same stirring speed and 0.3MPa pressurization conditions, 15kg / t of reducing agent sodium bisulfite is added, and the solution is filtered and washed with water until the pH value of the cleaning liquid is close to neutral to obtain relatively pure white carbon black. The leached slag is crushed, ground and sieved, and the particle size is controlled to be below 5mm, and then magnetic separation is carried out under a high-frequency electromagnetic field with a magnetic field intensity of 1000kA / m to obtain high-purity white carbon black.

[0076] (4) Add the Fe 3+Hydroxylamine with a corresponding molar content is stirred at 60°C for 20 minutes to be fully reduced, and then 60 kg of methyl trioctyl ammonium chloride is added to carry out a complex reaction. After fully reacting for 10 minutes, heavy metal precipitates such as As and Pb are generated. The precipitated impurities are separated by hot filtration, and then the copper ions are precipitated by an oscillating flow reaction. After filtering, washing and drying, matte is formed, and a filtrate is obtained at the same time;

[0077] (5) Add 20 L of 1 mol / L glycine solution to the filtrate, evaporate and concentrate at 80°C, reduce the volume to 1 / 2 of the volume of the filtrate, recover HCl vapor and recycle, precipitate high-purity ferrous chloride crystals from the obtained concentrated solution after cooling for 20 minutes, dissolve the precipitated ferrous chloride crystals and perform secondary crystallization to further improve the crystal purity; dry the purified ferrous chloride crystals in a gas atmosphere containing N2 at 80°C for 1 hour with hot nitrogen circulation to obtain ferrous fine chemical products. ;

[0078] The mother liquor after evaporation and concentration was added with 28kg N263 complexing agent, and after sufficient reaction, the zinc slag was obtained after filtration and drying;

[0079] After testing, the purity of SiO2 in white carbon black is 97.5%, and the silicon recovery rate is 98%; the purity of FeCl2 product is 99.4%, and the iron recovery rate is 94%; the copper grade of matte is 65.0%, and the copper recovery rate is 72%; the purity of zinc is 80.8%, and the zinc recovery rate is 86%.

[0080] Comparative Example 1

[0081] A method for treating valuable metals in copper slag tailings comprises the following specific steps:

[0082] (1) Pretreatment of copper slag tailings: 500 kg of copper slag tailings after pyrometallurgical copper flotation, containing 43.3% Fe, 14.4% Si, 2.3% Ca, 2.4% Zn, 1.1% Al, 0.24% Cu, and 0.08% As, were screened to remove agglomerated impurities with large particle sizes and adjust the particle size distribution, and then dried to reduce the humidity of the material and improve the subsequent acid leaching efficiency;

[0083] (2) adding the pretreated copper slag tailings into a 38% hydrochloric acid solution at a solid-liquid ratio of 1:5, and immersing the solution at 85° C. without ultrasonic assistance for 3 h, with the stirring speed controlled at 250 r / min, to fully dissolve the valuable metals in the leached residue to obtain a leaching solution and leached residue;

[0084] (3) The acid-leached filter residue is placed in a container with a certain pressure resistance, and tap water is added at a solid-liquid ratio of 1:2.5. The tap water is heated to boiling in the container, and the container wall is rinsed with cold water to quench it, thereby creating a boiling condition, the temperature is 60°C, the boiling time is 1h, and the rotor speed is 250rpm; the operating parameters of microwave heating and hydrofluoric acid pressure dissolution method purification are as follows: the microwave frequency range is 50GHz, the wavelength is 5mm, the leached residue is prepared into a slurry with a solid mass fraction of 20% and is placed in a pressure vessel equipped with a mechanical stirrer, 100kg of 40% hydrofluoric acid solution is added, and the leached residue is slurried. The slag and solution are stirred for 1 hour under microwave-assisted heating conditions at 150°C, and then the microwave device is turned off. The leached slag and solution are heated to 60°C in a water bath and stirred for more than 30 minutes. Then, under the same stirring speed and 0.3MPa pressurization conditions, 15kg / t of reducing agent sodium bisulfite is added, and the solution is filtered and washed with water until the pH value of the cleaning solution is close to neutral to obtain relatively pure white carbon black. The leached slag is crushed, ground and sieved, and the particle size is controlled to be below 5mm, and then magnetic separation is carried out under a high-frequency electromagnetic field with a magnetic field intensity of 1000kA / m to obtain high-purity white carbon black.

[0085] (4) Add the Fe 3+ The hydroxylamine with the corresponding molar content is stirred at 60°C for 20 minutes for full reduction, and then 35 kg of oxalic acid is added for complex reaction. After full reaction for 10 minutes, heavy metal precipitates such as As and Pb are generated. The precipitated impurities are separated by hot filtration, and then the copper ions are precipitated by oscillating flow reaction. After filtration, washing and drying, matte is formed, and the filtrate is obtained at the same time;

[0086] (5) Add 20 L of 1 mol / L glycine solution to the filtrate, evaporate and concentrate at 80°C, reduce the volume to 1 / 2 of the volume of the filtrate, recover HCl vapor and recycle, and precipitate high-purity ferrous chloride crystals from the obtained concentrated solution after cooling for 20 minutes, dissolve the precipitated ferrous chloride crystals and perform secondary crystallization to further improve the crystal purity; dry the purified ferrous chloride crystals in a gas atmosphere containing N2 at 80°C for 1 hour with hot nitrogen circulation to obtain ferrous fine chemical products. ;

[0087] The mother liquor after evaporation and concentration was added with 28kg N263 complexing agent, and after sufficient reaction, the zinc slag was obtained after filtration and drying;

[0088] After testing, the purity of SiO2 in white carbon black is 77.6%, and the silicon recovery rate is 88%; the purity of FeCl2 product is 77.6%, and the iron recovery rate is 72%; the copper grade of matte is 31.5%, and the copper recovery rate is 36%; the zinc purity is 70.3%, and the zinc recovery rate is 61%; compared with Example 2, this example only has a single factor variable of "no ultrasonic assistance is added during the leaching stage", which is similar to the literature report. It can be seen from the relevant data that the direct inorganic leaching method has insufficient open-chain destructive effect on island silicates, the leaching capacity is limited, the ferrosilicon separation effect is greatly reduced, and the yield of other valuable metals also declines due to the low leaching rate.

[0089] Comparative Example 2

[0090] A method for treating valuable metals in copper slag tailings comprises the following specific steps:

[0091] (1) Pretreatment of copper slag tailings: 500 kg of copper slag tailings after pyrometallurgical copper flotation, containing 43.3% Fe, 14.4% Si, 2.3% Ca, 2.4% Zn, 1.1% Al, 0.24% Cu, and 0.08% As, were simply screened to remove agglomerated impurities with large particle sizes and adjust the particle size distribution, and then dried to reduce the moisture content of the material and improve the subsequent acid leaching efficiency;

[0092] (2) adding the pretreated copper slag tailings into a 2 mol / L tannic acid solution at a solid-liquid ratio of 1:5, and immersing the solution under ultrasonic stirring at a temperature of 85° C. for 3 h, with the stirring speed controlled at 250 r / min, so as to fully dissolve the valuable metals in the leached residue to obtain a leachate and leached residue;

[0093] (3) The leached residue and circulating water are immersed in water at a solid-liquid ratio of 1:2.5, a temperature of 60°C, a time of 1 hour, and a rotation speed condition similar to the acid leaching step to further extract the residual valuable metals. The acid leached residue is placed in a container with a certain pressure resistance, and tap water is added at a solid-liquid ratio of 1:2.5. The tap water is heated to boiling in the container, and the container wall is rinsed with cold water to quench it, thereby creating a boiling condition. The temperature is 60°C, the boiling time is 1 hour, and the rotor speed is 250 rpm. A large amount of jelly-like gel is precipitated after filtering and washing with water;

[0094] (4) Add the Fe 3+ The corresponding mole of hydroxylamine was stirred at 60°C for 20 min for full reduction;

[0095] (5) Add 20 L of 1 mol / L glycine solution to the filtrate, evaporate and concentrate at 80°C, reduce the volume to 1 / 2 of the volume of the filtrate, recover HCl vapor and recycle, and precipitate high-purity ferrous chloride crystals from the obtained concentrated solution after cooling for 20 minutes, dissolve the precipitated ferrous chloride crystals and perform secondary crystallization to further improve the crystal purity; dry the purified ferrous chloride crystals in a gas atmosphere containing N2 at 80°C for 1 hour with hot nitrogen circulation to obtain ferrous fine chemical products. ;

[0096] The mother liquor after evaporation and concentration was added with 28kg N263 complexing agent, and after sufficient reaction, the zinc slag was obtained after filtration and drying;

[0097] After testing, the purity of the FeCl2 product was 62.3%, and the iron recovery rate was 51%; the copper leaching rate in the mother liquor was measured to be 73%; the results showed that in the tannic acid leaching system, a large amount of silica gel was produced during the process of the tannic acid solution fully contacting the ferrous silicate in the copper slag tailings, which had a negative impact on the structural fragmentation effect of the ultrasonic-assisted method, not only increasing the difficulty of subsequent filtration and purification processes, but also the purity of the iron product obtained by the final roasting was only 2 / 3 of that in the hydrochloric acid ultrasonic-assisted embodiment, so compared with Example 2, there is a synergistic effect between the inorganic strong acid system and the ultrasonic-assisted method.

[0098] Comparative Example 3

[0099] like Figure 1 The present invention provides a method for utilizing valuable metal resources in copper slag tailings, comprising the following specific steps:

[0100] (1) Pretreatment of copper slag tailings: 500 kg of copper slag tailings after pyrometallurgical copper flotation, containing 40.3% Fe, 10.9% Si, 2.1% Ca, 2.4% Zn, 1.1% Al, 0.27% Cu, and 0.04% As, were simply screened to remove agglomerated impurities with large particle sizes and adjust the particle size distribution, and then dried to reduce the moisture content of the material and improve the subsequent acid leaching efficiency;

[0101] (2) adding the pretreated copper slag tailings into a 38% hydrochloric acid solution at a solid-liquid ratio of 1:5, and immersing them for 3 hours under ultrasonic stirring at a temperature of 105°C to effectively expose Fe3O4 in the iron-rich phase in the silicate gaps and fully contact with hydrochloric acid during the leaching process. The ultrasonic power is 500W, the stirring speed is controlled at 250r / min, and 0.5M H2O2 is added to promote the oxidation process, fully dissolve the valuable metals in the leached slag, and obtain a leachate and leached slag;

[0102] (3) leaching the leached residue with circulating water at a solid-liquid ratio of 1:2.5, at a temperature of 60° C., for 1 h, and at the same rotation speed as the acid leaching step to further extract the residual valuable metals, and then filtering, washing, and drying to obtain white carbon black;

[0103] (4) Add the Fe 3+ Hydroxylamine with a corresponding molar content is stirred at 60°C for 20 minutes to be fully reduced, and then 60 kg of methyl trioctyl ammonium chloride is added to carry out a complex reaction. After fully reacting for 10 minutes, heavy metal precipitates such as As and Pb are generated. The precipitated impurities are separated by hot filtration, and then the copper ions are precipitated by an oscillating flow reaction. After filtering, washing and drying, matte is formed, and a filtrate is obtained at the same time;

[0104] (5) adding 20 L of 1 mol / L glycine solution to the filtrate, evaporating and concentrating at 80° C. to reduce the volume to 1 / 2 of the volume of the filtrate, recovering the HCl vapor and recycling it, and precipitating high-purity ferrous chloride crystals from the obtained concentrated solution after cooling for 20 min, dissolving the precipitated ferrous chloride crystals and performing secondary crystallization to further improve the purity of the crystals; drying the purified ferrous chloride crystals in a gas atmosphere containing N2 at 80° C. for 1 h with hot nitrogen circulation to obtain a ferrous fine chemical product;

[0105] The mother liquor after evaporation and concentration was added with 28kg N263 complexing agent, and after sufficient reaction, the zinc slag was obtained after filtration and drying;

[0106] After testing, the purity of SiO2 in white carbon black is 88.3%, and the silicon recovery rate is 91%; the purity of FeCl2 product is 93.8%, and the iron recovery rate is 90%; the copper grade of matte is 57.0%, and the copper recovery rate is 63%; the zinc purity is 78.5%, and the zinc recovery rate is 81%; the separation efficiency of silicon by acid leaching cannot reach the ideal purity through the ultrasonic-assisted process. Through the cyclic boiling water leaching, microwave heating and hydrofluoric acid pressure dissolution purification and high-frequency electromagnetic field-assisted magnetic separation proposed in the present invention, the purity of the white carbon black product obtained after leaching the copper slag tailings can be further improved to reach the purity obtained by the commercial-grade gas phase method.

[0107] Comparative Example 4

[0108] like Figure 1 The present invention provides a method for utilizing valuable metal resources in copper slag tailings, comprising the following specific steps:

[0109] (1) Pretreatment of copper slag tailings: 500 kg of copper slag tailings after pyrometallurgical copper flotation, containing 40.3% Fe, 10.9% Si, 2.1% Ca, 2.4% Zn, 1.1% Al, 0.27% Cu, and 0.04% As, were simply screened to remove agglomerated impurities with large particle sizes and adjust the particle size distribution, and then dried to reduce the moisture content of the material and improve the subsequent acid leaching efficiency;

[0110] (2) adding the pretreated copper slag tailings into a 38% hydrochloric acid solution at a solid-liquid ratio of 1:5, and immersing them for 3 hours under ultrasonic stirring at a temperature of 105°C to effectively expose Fe3O4 in the iron-rich phase in the silicate gaps and fully contact with hydrochloric acid during the leaching process. The ultrasonic power is 500W, the stirring speed is controlled at 250r / min, and 0.5M H2O2 is added to promote the oxidation process, fully dissolve the valuable metals in the leached slag, and obtain a leachate and leached slag;

[0111] (3) The acid-leached filter residue is placed in a container with a certain pressure resistance, and tap water is added at a solid-liquid ratio of 1:2.5. The tap water is heated to boiling in the container, and the container wall is rinsed with cold water to quench it, thereby creating a boiling condition, the temperature is 60°C, the boiling time is 1h, and the rotor speed is 250rpm; the operating parameters of microwave heating and hydrofluoric acid pressure dissolution method purification are as follows: the microwave frequency range is 50GHz, the wavelength is 5mm, the leached residue is prepared into a slurry with a solid mass fraction of 20% and is placed in a pressure vessel equipped with a mechanical stirrer, 100kg of 40% hydrofluoric acid solution is added, and the leached residue is slurried. The leached residue and the solution are stirred at 150°C for 1 hour under microwave-assisted heating conditions, and then the microwave device is turned off, and the leached residue and the solution are heated to 60°C in a water bath and stirred for more than 30 minutes, and then 15kg / t of reducing agent sodium bisulfite is added under the same speed stirring and 0.1-0.5MPa pressure conditions, and the solution is filtered and washed with water until the pH value of the washing solution is close to neutral, so as to obtain relatively pure white carbon black; the leached residue is crushed, ground and sieved, and the particle size is controlled to be less than 5mm, and then magnetic separation is carried out under the assistance of a high-frequency electromagnetic field with a magnetic field strength of 1000kA / m, and high-purity white carbon black is obtained after magnetic separation;

[0112] (4) adding 60 kg of methyl trioctyl ammonium chloride to the leachate to carry out a complex reaction, and fully reacting for 10 minutes to generate heavy metal precipitates such as As and Pb, filtering while hot to separate the precipitated impurities, and then oscillating the flow reaction to precipitate copper ions, filtering, washing, and drying to form matte, and obtaining a filtrate at the same time;

[0113] (5) adding 20 L of 1 mol / L glycine solution to the filtrate, evaporating and concentrating at 80° C. to reduce the volume to 1 / 2 of the volume of the filtrate, recovering the HCl vapor and recycling it, and precipitating high-purity ferrous chloride crystals from the obtained concentrated solution after cooling for 20 min, dissolving the precipitated ferrous chloride crystals and performing secondary crystallization to further improve the purity of the crystals; drying the purified ferrous chloride crystals in a gas atmosphere containing N2 at 80° C. for 1 h with hot nitrogen circulation to obtain a ferrous fine chemical product;

[0114] The mother liquor after evaporation and concentration was added with 28kg N263 complexing agent, and after sufficient reaction, the zinc slag was obtained after filtration and drying;

[0115] After testing, the purity of SiO2 in white carbon black is 97.5%, and the silicon recovery rate is 98%; the purity of FeCl2 product is 75.6%, and the iron recovery rate is 92%; the copper grade of matte is 54.0%, and the copper recovery rate is 61%; the zinc purity is 59.7%, and the zinc recovery rate is 71%; since electron-rich materials are not used to effectively reduce the trivalent iron ions in the mother liquor, the separation effect of other valuable metal elements is also greatly reduced, and the quality of the obtained resource products is significantly reduced, which is not conducive to effective value recovery.

[0116] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for resource utilization of valuable metals in copper slag tailings, characterized in that: The specific steps include: (1) treating the copper slag tailings by ultrasonic acid leaching to obtain a leaching solution and leaching residue; (2) subjecting the leached residue of step (1) to sequential purification by cyclic boiling water leaching, microwave heating with hydrofluoric acid pressure dissolution method and high-frequency electromagnetic field assisted magnetic separation to obtain high-purity white carbon black; (3) subjecting the leaching solution of step (1) to electron-rich material reduction and complexation treatment, and then obtaining matte and filtrate by oscillating flow reaction precipitation method; (4) The filtrate in step (3) is subjected to evaporative crystallization to obtain ferrous salt crystals and a concentrated mother liquor, the ferrous salt crystals are dried by hot nitrogen circulation to obtain FeCl2, and a complexing agent is added to the concentrated mother liquor to obtain zinc slag.

2. The method for resource utilization of valuable metals in copper slag tailings according to claim 1, characterized in that: In the ultrasonic acid leaching in step (1), the solid-liquid ratio is 1:2-20, the ultrasonic power is 300-800W, the temperature is 55-105°C, the leaching time is 2-5h, and the stirring speed is 50-250rpm; The acid leaching uses hydrochloric acid, nitric acid, sulfuric acid or a mixture of two of them.

3. The method for resource utilization of valuable metals in copper slag tailings according to claim 2, characterized in that: The mass concentration of the acid is 20-100%.

4. The method for resource utilization of valuable metals in copper slag tailings according to claim 1, characterized in that: The copper slag tailings also include pretreatments of screening and vacuum drying before ultrasonic acid leaching.

5. The method for resource utilization of valuable metals in copper slag tailings according to claim 1, characterized in that: The ultrasonic acid leaching in step (1) further comprises adding an oxidant, wherein the molar ratio of the oxidant to the iron element actually measured in the copper slag tailings is 1-3:

1.

6. The method for resource utilization of valuable metals in copper slag tailings according to claim 1, characterized in that: The operation steps of the cyclic bumping water immersion in step (2) are as follows: adding tap water to the leached residue at a solid-liquid ratio of 1:1-5, heating the tap water to boiling, and cooling it down with cold water to create bumping conditions, with a bumping time of 1-3 hours and a rotor speed of 50-250 rpm; The microwave heating assisted hydrofluoric acid pressure dissolution method purification operation steps are: after the leaching residue is prepared into a slurry with a solid mass fraction of 20-80%, a hydrofluoric acid solution is added, and the mixture is stirred for 1-2 hours under microwave assisted heating conditions; Then the microwave device is turned off, the mixed slurry is maintained at 55-85°C, and stirring is continued for more than 30 minutes. Then, a reducing agent is added for reduction under stirring and pressurizing conditions, and finally, the mixture is washed with filtered water until the pH value of the washing liquid is close to neutral, thereby obtaining relatively pure white carbon black; The frequency range of the microwave is 1-50 GHz, the wavelength is 1 mm-1 m, the amount of hydrofluoric acid added is 1-10% of the mass of the slurry, the temperature of the microwave-assisted heating is 150-250° C., the stirring speed is 250-500 rpm, the pressurization condition is 0.1-0.5 MPa, and the reducing agent is sodium bisulfite, and the amount added is 10-20 kg / t of the batching ratio; The magnetic field strength of the high-frequency electromagnetic field-assisted magnetic separation is 480-1600 kA / m. The relatively pure white carbon black is first crushed, ground and sieved before magnetic separation to control the particle size below 5 mm, and high-purity white carbon black is obtained after magnetic separation.

7. The method for resource utilization of valuable metals in copper slag tailings according to claim 1, characterized in that: The electron-rich material in step (3) includes at least one of hydroxylamine, metal organic framework material, quinone hydroquinone, organic acid and boron; the amount of the electron-rich material added and the Fe content in the leaching solution are 3+ The molar amounts in are equal, the reaction temperature is 30-50°C, and the time is 20 min; The molar ratio of the complexing agent to the zinc element measured in the leaching solution is 1-1.5:1; The complexing agent is selected from methyl trioctyl ammonium chloride and / or oxalic acid.

8. The method for resource utilization of valuable metals in copper slag tailings according to claim 1, characterized in that: The crystallization in step (4) is performed twice; The conditions of the evaporation concentration are: evaporation at 70-85°C, concentration to 1 / 3-1 / 2 of the volume of the filtrate; The gas atmosphere of the hot nitrogen circulation drying is N2, and the conditions are: 50-200°C circulation drying for more than 1h; The concentrated mother liquor is diluted to Zn 2+ After the concentration reaches 1 g / L, the pH is adjusted to 2-5 and then the complexing agent is added; The complexing agent is N263 and / or P2O4, and the final concentration of the added amount is 0.6-1M.

9. The method for resource utilization of valuable metals in copper slag tailings according to claim 1, characterized in that: In step (4), a buffer solution is added to the evaporation crystals; Fe is measured in the buffer solution and the filtrate. 3+ The molar ratio is 1-1.3:1; The buffer solution is at least one of glycine, acetic acid, citric acid and EDTA.

10. The method for resource utilization of valuable metals in copper slag tailings according to claim 1, characterized in that: The copper slag tailings are tailings after pyrometallurgical copper smelting flotation, and their main chemical compositions are Fe43-45%, Ca 0.6-2.8%, Zn 1.2-2.5%, Cu 0.27-3.1%, Al 1.8-2.3% and Si 15-21%.

Citation Information

Patent Citations

  • Method for comprehensively recovering Fe, Cu and Si from copper smelting slag

    CN101555551A